2010
DOI: 10.1111/j.1365-313x.2010.04146.x
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-like kinase OsSIK1 improves drought and salt stress tolerance in rice (Oryza sativa) plants

Abstract: SUMMARYReceptor-like kinases (RLKs) play essential roles in plant growth, development and responses to environmental stresses. A putative RLK gene, OsSIK1, with extracellular leucine-rich repeats was cloned and characterized in rice (Oryza sativa). OsSIK1 exhibits kinase activity in the presence of Mn 2+, and the OsSIK1 kinase domain has the ability to autophosphorylate and phosphorylate myelin basic protein (MBP). OsSIK1 promoter-GUS analysis revealed that OsSIK1 is expressed mainly in the stem and spikelet i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
203
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(208 citation statements)
references
References 61 publications
5
203
0
Order By: Relevance
“…DEGs on the introgressed regions of RM262 on chromosome 2, RM432 on chromosome 7, and RM38 on chromosome 8 were largely related to signal transduction cascades. These genes included genes encoding terpene synthase (Os02g36140, Os08g07100), protein phosphatase 2C (Os07g32380), and receptor-like kinase OsSIK1 (Os08g02996), which are known to be strongly associated with abiotic stress response [43,45,46]. Strikingly, a gene cluster containing four PCD-related genes were co-localized on the introgressed region of chromosome 11 (Additional file 17), indicating their distinct role in CT of K354.…”
Section: Resultsmentioning
confidence: 99%
“…DEGs on the introgressed regions of RM262 on chromosome 2, RM432 on chromosome 7, and RM38 on chromosome 8 were largely related to signal transduction cascades. These genes included genes encoding terpene synthase (Os02g36140, Os08g07100), protein phosphatase 2C (Os07g32380), and receptor-like kinase OsSIK1 (Os08g02996), which are known to be strongly associated with abiotic stress response [43,45,46]. Strikingly, a gene cluster containing four PCD-related genes were co-localized on the introgressed region of chromosome 11 (Additional file 17), indicating their distinct role in CT of K354.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, OsSIK1, a receptor-like kinases (RLKs) overexpression in rice also showed higher tolerance to salt stresses compared with WT through the activation of its antioxidative system (Ouyang et al, 2010). Thus, the overexpression of 35S::AtSIA1 lines improve plant tolerance to high salinity, which may be due to the regulation of ROS balance.…”
Section: Discussionmentioning
confidence: 97%
“…Many naturally salt tolerant plants have been shown molecular, physiological, developmental and morphological characteristics of evolved adaptive mechanisms at multiple levels. Generally, as the earliest response regulatory genes, protein kinase plays a central role in the regulation of environmental adaptability (Ouyang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpressed OsSIK1 rice plants showed tolerance to oxidative, drought and salt stress by inducing antioxidant system. It was observed that the activity of antioxidants enzymes like catalase, super-oxide dismutase and peroxidases was higher in overexpressed rice plants with subsequent lower level of H2O2 (Ouyang et al, 2010).…”
Section: Drought Signal Perception and Rosmentioning
confidence: 99%